Desvelando histórias de alunas (os) trabalhadoras (es) do PMEA: indícios para construção de uma EJA democrática e dialógica - Silva, Rafael Domingues da (2014)
This work, a qualitative research, aimed to analyze the life history and schooling history of working students enrolled in the Programa Municipal de Erradicação do Analfabetismo-PMEA (Municipal Program for the Illiteracy Eradication), checking in the learners\' speech the words that canbe used as generating themes of questioning, in order to provide contributions to the configuration of a Youth and Adults Education that do not mute their students, that is to say, a dialogical and problem-posing educational praxis. Supported in the formulations of Freire (1989) (1994) (2002) (2007) (2008) (2011), as well as Gadotti (1995), Gramsci (1978) and Haddad (1985), were used as instruments for data producing the documents\' analysis, Group Interview, the « Discussions Circle and the observation ofthe classroom\'s activity, by means of fieldwork conducted during the school year 2013 in the Lírios do Campo School, located in Uberlândia, Minas Gerais State. We concluded that the great majority of students in the PMEA had a very short educational experience, being excluded from the school as a result of the inequalities of opportunities. We verified that they all had a rural childhood and adolescence, characterized by acute poverty. They moved to the city, setting up a population phenomenon verified in the country called rural exodus, with the hope to have better life conditions. However, this change did not guarantee life and scholar conditions improvement. The motivations which caused their return to the studies are multiples, like personal will, the dream of studying, the realization of plans, to achieve goals like getting a driver\'s license, become more independent in their own business, be a \"obreiro\" (an active participant) in church, remove from personal documents the information that the holder \"is illiterate\", etc. Such reasons are directly or indirectly linked to the job market, even if they haven\'t made explicit this information or even denied the return to school as an obligation. We realized that the thematic axes contained in the Caderno de Orientações (Guidelines Booklet) were not conceived from the working students\' worldview and culture, but were designed for an education to the job market. We affirm that students have a traditional and banking conception of the class, where the teacher\'srole is to work with them to break out with this logic. The exercise of reproduction is changed by the production of knowledge. We also noticed that the words collected during the fieldwork and by means of the instruments reflect the lifestyle of that male and female students, providing us the elements to elaborate some contributions that may cause discussions, moving towards a possible practice of a non-banking education, that is to say, to overcome the contradictions between educator and students.